Accounting Information and Financial Decision Making in Organizations in Kabale District. - Taritureka, Nobert (Kabale University, 2024)
The study examined the role of accounting information in financial decision-making within organizations in Kabale District, guided by three objectives: to assess the impact of transaction processing systems on organizational decision-making, to evaluate the influence of decision support systems on decision-making, and to explore the relationship between information systems and decision-making in these organizations. A sample of 80 respondents participated in the research, which employed both qualitative and quantitative approaches. Data collection methods included interviews and questionnaires. The findings revealed that information systems, particularly transaction processing systems, significantly enhance decision-making by efficiently managing a large number of operations simultaneously. The study recommended that organizations invest in improving the functionality of transaction processing systems through increased funding and better management, as this would enhance cost management and overall decision-making efficiency. The study concluded that all objectives were successfully addressed. The first objective demonstrated that transaction processing systems play a vital role in decision-making. Proper utilization of these systems is likely to improve cost management practices within financial institutions, thereby contributing to better financial decision-making processes.